Towards a postural wellness program for the employees and students of the University of Baguio - Dapiawen, Aida A.; Fernandez, Ruth D.; Mallillin, Rustico Natale N. (2015)
Good posture entails the use of proper body mechanics in the performance of daily activities. Without proper body mechanics, repeated movements can place undue stress within joints leading to various musculoskeletal symptoms. Posture is the alignment of the body parts whether upright, sitting, or recumbent. Good posture is having the spine or backbone in neutral alignment during performance of tasks. Impairments in the joints and soft tissues may lead to faulty posture; or conversely, faulty poses may harm joints and soft tissues leading to discomfort and pain. The goal of the study was to develop a postural wellness program for the employees and students of the University of Baguio. Specifically, it looked into the profile of the employees and students along a) Antero- Posterior View, b) Lateral View, and c) Forward Bending Test. It also identified the complaints of the employees and students associated with body pains and how they managed these. This was an exploratory study that utilized primarily descriptive-survey. Two hundred eighty- one (281) respondents have subjected themselves to the postural assessment activity on August 3, 5 and 6, 2013 as part of the University of Baguio’s celebration of its Foundation Day. It has been found out that a big percentage (85%) of the participants have some degree of postural deviations or asymmetries. This finding poses a concern for the postural wellness of the employees and students of the University. The participants manifested with postural faults most commonly along the anteroposterior view and subsequently along lateral view and forward bending test. Back ache is the most common area of complaint associated with body pains. Poor posture and incorrect practice of body mechanics have been found to possibly contribute to the musculoskeletal symptoms. Respondents usually result to self-care such as purchasing over-the-counter drugs and having massage sessions as a way of pain management.
Keywords: Health programs